Differences in the impact of impaired glucose status on clinical outcomes in younger and older adults: Over a decade of follow-up in the Tehran lipid and glucose study - Asgari, Samaneh; Masrouri, Soroush; Khalili, Davood; Azizi, Fereidoun; Hadaegh, Farzad (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Studies found that the impact of dysglycemia on microvascular, macrovascular events and mortality outcomes were different between the younger versus older population. We aimed to investigate the age-specific association of prediabetes with clinical outcomes including type 2 diabetes (T2DM), hypertension, chronic kidney disease (CKD), cardiovascular disease (CVD), and mortality. Materials and methods: A total of 5970 Iranians (3829 women) aged ≥30 years, without T2DM, were included. The age-specific (<60 and ≥ 60 years; minimum p-value for interaction=0.001) multivariable-adjusted Cox regression was done to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) of the impaired glucose status including impaired fasting glucose (IFG) vs. normal fasting glucose (NFG), impaired glucose tolerance (IGT) vs. normal glucose tolerance (NGT), and IFG& IGT vs. NFG/NGT with each outcome. Results: Among individuals aged ≥60 years, the prevalence of impaired glucose status (IFG, IGT, or both) was about 2 times higher compared to those aged <60. Age-specific association between prediabetes and incident hypertension was found for those aged <60 years; [HR (95% CI); IFG: 1.38(1.16-1.65), IGT: 1.51(1.26-1.81), and IFG & IGT: 1.62(1.21-2.12)]. For CVD, in all impaired glycemic states, those aged <60 were at higher significant risk [IFG: 1.39 (1.09-1.77), IGT: 1.53(1.19- 1.97), and IFG&IGT: 1.60 (1.14-2.25)]. Stratified analyses showed similar associations for IFG and IGT with non-CV mortality 1.71(1.04-2.80) and 2.12 (1.30-3.46), respectively as well as all-cause mortality among those aged <60 years [IFG: 1.63(1.08-2.45) and IGT: 1.82(1.20-2.76)]. In both age groups, all glycemic status were significantly associated with T2DM but not with CKD and CV mortality. Conclusions: The high prevalence of prediabetes particularly among the elderly population, limited resources, and the observed significant age differences in the impact of prediabetes states on different clinical outcomes calls for multicomponent intervention strategies by policy health makers, including lifestyle and possible pharmacological therapy, with the priority for the young Iranian population.